An Analysis of Repetition Style in the Qur'an According to Al-Tabari's Commentary - Laelani, Lilih; Komarudin, Edi (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2023)
Repetition (al-Tikrar) is one of the language styles used in the Qur'an. Currently, many hufadz of the Qur'an start memorizing from surah 30. The problem is that as a Muslim, he must increase his interaction with the Qur'an from reading, memorizing, understanding and practicing it. The purpose of this research is to know and understand the meaning of repetition style in the Qur'an based on the theory of qawa'id at Tafsir by Uthman al Sabt, to identify and know the letters in chapter 30 which contains At Tikrar's rules, to understand the analysis of At Tikrar's rules. Researchers conducted this research through library research with a qualitative descriptive analysis research type. The researcher used the main source of the book Qawa'id at Tafsir, Jam'an wa Dirasatan by Khalid bin 'Utsman Al-Sabt. Secondary sources are the Al-Qur'an Juz 'Amma (juz 30) and the Book of Tafsir Jami' al Bayan 'an Ta'wil Ay al-Qur'an by Imam Al-Tabari. This study found that the language style of At Tikrar in Al Qur'an Juz 30 is found in 35 of the 37 surahs al mufashalat (short). In almost all surahs there are verses, sentences, or words that are repeated, either in pronunciation or editorial or repetition of meaning, except for two surahs that do not have repetition of meaning or lafazh, namely the 105th Surah Al-Fil and the 108th Surah Al-Kauthar.